Factors Influencing Referral to Maternity Models of Care in Australian General Practice - Thomas, Jaime (Curtin University, 2023)
General practitioners (GP) play a vital role in referring prospective parents to a maternity model of care. Despite their gatekeeping role, there is limited research exploring the referral process from the GP perspective. A qualitative descriptive approach was undertaken to explore and describe the factors influencing Australian GPs' decision-making when referring pregnant women to maternity models of care. Both GP and Women's Factors' influence referral decisions, Primary Healthcare Networks are critical to addressing gaps.